2003
DOI: 10.1016/s0896-6273(03)00465-3
|View full text |Cite
|
Sign up to set email alerts
|

Place Representation within Hippocampal Networks Is Modified by Long-Term Potentiation

Abstract: In the brain, information is encoded by the firing patterns of neuronal ensembles and the strength of synaptic connections between individual neurons. We report here that representation of the environment by "place" cells is altered by changing synaptic weights within hippocampal networks. Long-term potentiation (LTP) of intrinsic hippocampal pathways abolished existing place fields, created new place fields, and rearranged the temporal relationship within the affected population. The effect of LTP on neuron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
145
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 46 publications
18
145
2
Order By: Relevance
“…Passive rotation has been shown to modulate the activity of place cells [62,63] while bilateral vestibular inactivation or damage abolished location-specific firing of place cells [64,65]. We suggest here that vestibular stimulation enhanced hippocampal LTP, which may be necessary for the formation of place fields [66][67][68]. Degradation of hippocampal place fields during walking by cholinergic blockade [69] suggests that acetylcholine in the hippocampus is involved in place field formation, perhaps by enhancing LTP.…”
Section: Vestibular Stimulation Enhances Ltpmentioning
confidence: 63%
“…Passive rotation has been shown to modulate the activity of place cells [62,63] while bilateral vestibular inactivation or damage abolished location-specific firing of place cells [64,65]. We suggest here that vestibular stimulation enhanced hippocampal LTP, which may be necessary for the formation of place fields [66][67][68]. Degradation of hippocampal place fields during walking by cholinergic blockade [69] suggests that acetylcholine in the hippocampus is involved in place field formation, perhaps by enhancing LTP.…”
Section: Vestibular Stimulation Enhances Ltpmentioning
confidence: 63%
“…The hippocampal representation can be altered by modification of long-term potentiation (LTP) (Rotenberg et al, 2000;Dragoi et al, 2003), and this synaptic plasticity can be modulated by dopamine (Otmakhova and Lisman, 1996; Matthies et al, 4 (Figure legend continued. ) C, A place cell had a place field that followed the change of both the distal cues (1-2) and proximal cues (3-4) in the familiar environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the HF appears to provide a neural representation of physical space, although broader functions have also been suggested (Maguire et al, 1998;Eichenbaum et al, 1999). The place-cell representation of space is thought to underlie certain forms of spatial learning (McHugh et al, 1996(McHugh et al, , 2007Cho et al, 1998;Kentros et al, 1998;Eichenbaum et al, 1999;Rotenberg et al, 2000;Dragoi et al, 2003). It was found that dopamine D 1 receptor knock-out (D1R-KO) mice had impaired spatial learning and altered spatial activity in the nucleus accumbens (El-Ghundi et al, 1999, Tran et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental induction of LTP will surely disturb the synaptic changes taking place during associative learning in selected neural sites. Indeed, it is known that LTP saturation of hippocampal circuits disrupts spatial learning (Barnes et al, 1994), and that place representation in hippocampal networks can be modified experimentally by LTP (Dragoi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%